PENDAMPINGAN PEMBUATAN MARKET PLACE E-COMMERCE BAGI PELAKU UMKM GULA MERAH DI DESA LEBAK PARAHIYANG LEUWIDAMAR LEBAK - Abdul Bahits; Eneng Marliawati; Nurul Agnestya Putri Salma; Alief Rifaldi; Sri Haryati (Indonesian Collaboration Journal of Community Services, 2022)
Lebak Parahiyang Village is one of the developing villages. The problem faced by Lebak Parahiyang Village in terms of SMEs, especially by brown sugar producers is the lack of a significant level of sales, because according to them it is difficult to find a wider market share. Therefore, one way to increase the level of sales is by making attractive product packaging so that it has a selling value then utilizing technology in the form of an E-Commerce marketplace. With the use of the E-commerce marketplace as an initial boost to get significant changes and business development for brown sugar producers in the village of Lebak Parahiyang